Riset Kepuasan Konsumen UMKM Kuliner Kampung Ujung Labuan Bajo - Kristoforus Toni Harjo (Pusat Penelitian dan Pengabdian Politeknik eLBajo Commodus, 2024)
This study aims to evaluate the customer satisfaction of culinary MSMEs in Kampung Ujung, Labuan Bajo, focusing on three main factors: environment, price, and service quality. Kampung Ujung is a growing culinary center, attracting many domestic and foreign tourists. This research uses quantitative methods with data collection techniques through questionnaires, observations, interviews, and documentation studies. Data analysis was conducted using multiple linear regression analysis to test the influence of independent variables on customer satisfaction. The results showed that service quality and price have a significant influence on customer satisfaction, with price showing a negative influence. In contrast, the environment shows a positive but insignificant effect. The coefficient of determination shows that the model used is able to explain 61% of the variability in customer satisfaction. The T-test and F-test also support the finding that price and service quality are the main factors that significantly affect customer satisfaction. This research provides important insights for MSME players and the government in improving service quality and pricing strategies to increase customer satisfaction. In conclusion, improving service quality and effective price management are essential to maintain and increase customer satisfaction in the culinary sector of MSMEs in Kampung Ujung, Labuan Bajo. Keywords: Customer satisfaction, MSMEs